Desain dan Pembuatan Faceshield Sebagai Alat Perlindungan Diri Penyebaran Covid19 - Cahyo Budi Nugroho; Muhammad Ismail; Gawan Sagoro; Abulija Maskarai; Muhammad Syafei Gozali; Asrafi Asrafi; Sapto Wiratno Satoto; Randy Saputra; Chandra Defta Rusdwinanto; Sriyanto Sriyanto; Naufal Abdurrahman Prasetyo; Meida Perwira Antartika (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
The need for personal protective equipment (PPE) in the form of face protection has increased sharply since the spread of the covid19. Viruses that can be transmitted through droplet media can endanger health or personal who interact directly with sufferers of diseases caused by covid19. The existence of a face shield, even though it is not the only one protective device, is needed to support other equipment. Without the face shield, it will increase the likelihood the transmission of virus. The purpose of writing this journal is to explain the process of design, manufacture and planning of PPE distribution to the public From the process carried out it can be concluded that the production process goes through several stages involving human resources with product design, managerial, packaging ability and also diverse tool resources including pneumatic, CNC machines, laser cutting and computer. In terms of distribution, delivery of equipment is carried out using a variety of land, sea and air expeditions with location areas in several provinces including Central Java, East Java, West Java, West Sumatra and Riau Islands.